Strategi Pembiasaan Guru dalam Menanamkan Akhlak pada Anak Usia Dini - Maratus Sholekah, Inten Temu (PT Faliha Cendekia Nusantara, 2024)
The moral crisis is a major polemic for the Indonesian nation today. As we see on television and other social media, there are many cases such as murder, bullying, brawls, violence, lack of courtesy towards older people. Therefore, it is necessary to instill morals from an early age. Because morals that are instilled from an early age will continue to develop into the next age. The aim of this research is to determine the application of teachers' habituation strategies in instilling moral values in children aged 5-6 years at the Al Battani Mranggen Kindergarten and to determine the supporting and inhibiting factors for the habituation strategies used by teachers. The research method used is descriptive qualitative research. The data sources consist of primary data (teachers) and secondary data (strategic location of the kindergarten, teacher names, and other data). From the research results, it is clear that teachers' habituation strategies in instilling moral values in children aged 5-6 years at Al Battani Kindergarten are dhuha prayers in congregation, reading prayers before eating and drinking, murojaah or memorizing short letters, short hadiths, short prayers and toyyibah sentences. , and shaking hands and responding to greetings. The supporting factors for this habituation strategy are support from parents, commitment to the school community, and adequate facilities. The inhibiting factors are the different backgrounds of the participants and the environment or social interactions of the students.